Thermal regimes of lakes in the southern and eastern part of the Baltic Sea catchment area during the period of climate change - Skowron, Rajmund; Jaszczyk, Tomasz (Bulletin of Geography. Physical Geography Series, 2023)
The study covered eleven lakes located in northern Poland and Belarus, aiming to determine the degree and trends of surface water temperature changes for the years 1971–2020 and lake ice cover for the period of 1961–2020 under the influence of ongoing climate changes. The analysis focused on changes and trends in average monthly surface water temperatures (SWT), as well as changes in the onset and end, duration and maximum thickness of ice cover. The average annual surface water temperature increased in the lakes by an average of 0.044°C per year. The lake with the highest trend is Chervonoe, at with 0.066°C per year, while the lowest is 0.029°C per year in Lake Hańcza. The ice cover duration showed a decrease of 0.6 days per year, and there was a reduction in maximum ice thickness of 0.27 cm per year